2002
DOI: 10.1063/1.1515374
|View full text |Cite
|
Sign up to set email alerts
|

Optical constants of In0.53Ga0.47As/InP: Experiment and modeling

Abstract: Energy dependence of electron effective mass and effect of wave function confinement in a nanoscale In0.53Ga0.47As/In0.52Al0.48As quantum well

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…In order to calculate R 1 using the k⋅p theory we follow the procedure provided in Ref. [4], with the high frequency dielectric constant ε(∞) = 7.28 and the matrix element E p = 23 eV [7]. The results of this calculation are R 1 = 244, 253, 256, and 261 meV for beryllium compositions x = 0, 0.03, 0.10, and 0.19, respectively.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In order to calculate R 1 using the k⋅p theory we follow the procedure provided in Ref. [4], with the high frequency dielectric constant ε(∞) = 7.28 and the matrix element E p = 23 eV [7]. The results of this calculation are R 1 = 244, 253, 256, and 261 meV for beryllium compositions x = 0, 0.03, 0.10, and 0.19, respectively.…”
mentioning
confidence: 99%
“…References [8] and [9] have demonstrated that even if the E 0 exciton is not resolved, the Coulomb interaction still affects the band-to-band line shape. Thus, ε 2 (E) is given by [4] …”
mentioning
confidence: 99%
See 3 more Smart Citations